2013
DOI: 10.1017/s1431927613000329
|View full text |Cite
|
Sign up to set email alerts
|

Cell Adhesion, Multicellular Morphology, and Magnetosome Distribution in the Multicellular Magnetotactic Prokaryote Candidatus Magnetoglobus multicellularis

Abstract: Candidatus Magnetoglobus multicellularis is an uncultured magnetotactic multicellular prokaryote composed of 17-40 Gram-negative cells that are capable of synthesizing organelles known as magnetosomes. The magnetosomes of Ca. M. multicellularis are composed of greigite and are organized in chains that are responsible for the microorganism's orientation along magnetic field lines. The characteristics of the microorganism, including its multicellular life cycle, magnetic field orientation, and swimming behavior,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 23 publications
0
38
0
Order By: Relevance
“…Cells are asymmetrically flagellated, with the surface of the cell exposed to the surrounding environment and covered with numerous flagella (125,128). Most described MMPs are spherical (42,45,(124)(125)(126)129), although some are ovoid or pineapple shaped in morphology (121,130), and they all appear to possess a central, acellular compartment (124,129,131). Wall structures between cells similar to eukaryotic gap junctions have been described for one MMP (125).…”
Section: Deltaproteobacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Cells are asymmetrically flagellated, with the surface of the cell exposed to the surrounding environment and covered with numerous flagella (125,128). Most described MMPs are spherical (42,45,(124)(125)(126)129), although some are ovoid or pineapple shaped in morphology (121,130), and they all appear to possess a central, acellular compartment (124,129,131). Wall structures between cells similar to eukaryotic gap junctions have been described for one MMP (125).…”
Section: Deltaproteobacteriamentioning
confidence: 99%
“…Magnetosomes are usually loosely ar- ranged in short chains or clusters in individual cells (24,45,133,134,136), although there is a general-enough consensus in magnetosome arrangement that there is a net magnetic dipole moment to the entire unit (45,124). It has also been shown that magnetosome chain polarities of individual cells contribute coherently to the total magnetic moment of the MMP in a highly coordinated fashion, suggesting a remarkable degree of magnetic optimization, which is likely inherited by individual cells by a sophisticated reproduction mechanism (131,137).…”
Section: Deltaproteobacteriamentioning
confidence: 99%
“…Adhesion molecules and possibly calcium-dependent proteins have important roles in the unique morphology and life cycle of Ca. M. multicellularis (Keim et al, 2004b;Abreu et al, 2013). Thus, we examined the genome of Ca.…”
Section: Deciphering Mmps Through Genomicsmentioning
confidence: 99%
“…The cell and outer membranes of neighbour cells are juxtaposed, resembling mammalian cell-to-cell junctions (Keim et al, 2004a). Magnetosomes are arranged into one to five parallel chains (Abreu et al, 2008), forming planar groups which are close and parallel to the microorganism surface (Silva et al, 2007;Abreu et al, 2013). The cytoplasm contains about 80 magnetosomes (Abreu et al, 2008) containing iron sulphide crystals (Keim et al, 2004a) 88 6 11 nm in length and 65 6 10 nm in width (Abreu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Each cell presents about 30 flagella, 0.9-3.8 mm in length, clustered in the part of the cell that faces the environment (Silva et al, 2007). Cells and magnetosomes are arranged in such a way that the magnetosome chains are roughly parallel to each other in the whole microorganism (Abreu et al, 2013). Magnetosomes are arranged into one to five parallel chains (Abreu et al, 2008), forming planar groups which are close and parallel to the microorganism surface (Silva et al, 2007;Abreu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%